Guidance for homecare of children and teenagers in oral antineoplastic chemotherapy (Research, Society and Development, 2021)
Objectives: identify the oral antineoplastic chemotherapy most used by children and teenagers in outpatient treatment; and describe the guidance for homecare of children and teenagers that use antineoplastic chemotherapy using scientific literature as main source. Method: A descriptive study was performed in a federal hospital in the city of Rio de Janeiro, Brazil. The medical records of 45 children and teenagers in treatment using oral chemotherapy were analyzed from July to September of 2020. Results: The chemoteherapy used was mercaptopurine (29,1%), methotrexate (21%), imatinib (19,3%), temozolamide (9,7%), everolimus (8,1%), cyclophosphamide (6,4%), thioguanine (1,6%), etoposide (1,6%), topotecan (1,6%) and pazopanibe (1,6%). For each substance part of the chemotherapy the main guidance was listed for homecare of children and teenagers. Final considerations: This study allows the targeting of the guidance actions for homecare of children and teenagers in oral antineoplastic chemotherapy aiming to its accession and a higher safety in treatment.